Convenient Synthesis of New N-3-Substituted Pyrido[1′,2′:1,5]pyrazolo[3,4-d]pyrimidine-2,4(1H,3H)-dione Derivatives - Belaroussi, Rabia; El Bouakher, Abderrahman; Marchivie, Mathieu; Massip, Stéphane; Jarry, Christian; El Hakmaoui, Ahmed; Guillaumet, Gérald; Routier, Sylvain; Akssira, Mohamed (Synthesis, 2013)
Previously unknown N-3-substituted pyrido[1′,2′:1,5]pyrazolo[3,4-d]pyrimidine derivatives were synthesized by a straightforward four-step synthesis. Starting from a 1-aminopyridinium salt, dimethyl acetylenedicarboxylate condensation followed by a fully regioselective saponification led to a pyrazolo[1,5-a]pyridine monoester as a key intermediate. A Curtius rearrangement directly followed by amine condensation afforded a urea library. A final pyrimidine ring closure resulted in achievement of the heterocyclic construction. This straightforward strategy provides an efficient method to easily access a library of rare tricyclic scaffolds and highly valuable derivatives.
Keywords: pyrazolo[1,5-a]pyridines; regioselective hydrolysis; Curtius rearrangement; pyridopyrazolo[3,4-d]pyrimidines